Non-targeted effects induced by ionizing radiation: Mechanisms and potential impact on radiation induced health effects. Issue 1 (1st January 2015) - Morgan, William F.; Sowa, Marianne B.
Highlights Cell-to-cell communication between irradiated cells and non-irradiated cells (NTE's) and its potential impact on human health. Speculation on the factors that might be involved in communicating responses from irradiated cells to non-irradiated cells and eliciting an effect. Relationships between irradiated cells and non-irradiated cells and the implications for delayed health effects.